2015
DOI: 10.1002/cncr.29472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on outcomes after definitive dose‐escalated intensity‐modulated radiotherapy for localized prostate cancer

Abstract: INTRODUCTION Previous publications have shown conflicting results regarding body mass index (BMI) and prostate cancer (CaP) outcomes after definitive radiotherapy prior to the dose escalation era. Our goal is to determine whether increasing BMI is associated with CaP outcomes in men with localized CaP treated with dose escalated radiotherapy. METHODS We identified patients with localized (T1b-T4N0M0) CaP treated with definitive intensity modulated radiation therapy (IMRT) and image guidance (IGRT) from 2001–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Radiation therapy uses targeted ionizing radiation to destroy tumor cells. Among patients with prostate cancer, multiple studies of external‐beam radiation therapy have reported an association between obesity and inferior outcomes . Proposed mechanisms for this correlation include technical issues of delivering radiation therapy to obese patients, such as difficulty with daily set up and an increased likelihood of shifts in tumor location among obese patients .…”
Section: Obesity and Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy uses targeted ionizing radiation to destroy tumor cells. Among patients with prostate cancer, multiple studies of external‐beam radiation therapy have reported an association between obesity and inferior outcomes . Proposed mechanisms for this correlation include technical issues of delivering radiation therapy to obese patients, such as difficulty with daily set up and an increased likelihood of shifts in tumor location among obese patients .…”
Section: Obesity and Radiation Therapymentioning
confidence: 99%
“…Among patients with prostate cancer, multiple studies of external-beam radiation therapy have reported an association between obesity and inferior outcomes. 16 Proposed mechanisms for this correlation include technical issues of delivering radiation therapy to obese patients, such as difficulty with daily set up and an increased likelihood of shifts in tumor location among obese patients. 17 It has been reported that obese patients with cervical cancer also experience increased treatment-related toxicities compared with normal weight patients.…”
Section: Introductionmentioning
confidence: 99%
“…Obese patients tend to have larger interfractional shifts because of setup errors,142, 143 and anatomic variations in obese patients may lead to significant variations in delivered dose 144 . Obese patients also have been reported to have higher rates of prostate cancer recurrence after EBRT 145, 146. There is no direct evidence regarding the effectiveness of specific immobilization or IGRT techniques in obese patients.…”
Section: Techniques Of Patient Immobilization and Setupmentioning
confidence: 99%
“…Concerning the impact of AT on sensitivity to radiotherapy, the results remain controversial since some studies have shown an adverse effect of obesity on clinical outcome of prostate cancer patients [ 171 173 ], while other reports have indicated no difference in efficacy between obese and lean patients in prostate and esophageal cancers [ 174 176 ]. By contrast, the link between obesity and resistance seems to be more firmly established for chemotherapy and endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%